Kebijakan Perlindungan Profesi Guru terhadap Tindak Krimilitas - Amalia, Ulfiyana; Ufairoh, Fania (ARZUSIN, 2022)
This study examines the problem of criminal acts against educators that often occur recently in the world of education. The purpose of writing this article is to explain how the policy is in the form of legal protection of teachers against criminal acts, as well as explain how the position of teachers themselves in the profession and explain what the code of ethics that teachers must have. Because what we know, the last few decades of teachers in carrying out their duties have often become subjects. Of course this is due to rampant acts of violence that occur, especially in schools. Whether that is done by students, parents and even school administrators to the teachers themselves. The method in this article research uses a qualitative method with a literature review approach, as well as interpreting and comparing several literatures that discuss the policy of protecting the teaching profession against criminal acts. The result of writing this article is that teachers in carrying out their obligations as educators are often faced with more complex problems where these problems also often occur when teachers are disciplining students, parents of students and the community are often affected by the existence of doctrine. about child protection. Actually, in Law No. 14 of 2005 concerning Teachers and Lecturers, there has been a discussion on the rights and protection and guarantees for the teaching and lecturer profession. However, nowadays, the law is not fully realized.